SOME QUESTIONS ON EXTERNAL DEFINABILITY - B.S. Baizhanov; S.S. Baizhanov (Academic Scientific Journal of Computer Science, 2019)
The article discusses the various approaches to the concept of external definability developed in ominimal theories. An example of o-minimal theories shows how external constants help determine the existence of a solution in a model of a formula with external constants. The basic concepts are formulated with the help of which external definability is proved. A brief review of the results for dependent theories is given. In conclusion, sufficient conditions are formulated so that the NSOP theory has the some property of external definability. A brief explanation of the stated theorem is given.